An outlook on using serial femtosecond crystallography in drug discovery. (2nd September 2019) - Mishin, Alexey; Gusach, Anastasiia; Luginina, Aleksandra; Marin, Egor; Borshchevskiy, Valentin; Cherezov, Vadim
ABSTRACT: Introduction : X-ray crystallography has made important contributions to modern drug development but its application to many important drug targets has been extremely challenging. The recent emergence of X-ray free electron lasers (XFELs) and advancements in serial femtosecond crystallography (SFX) have offered new opportunities to overcome limitations of traditional crystallography to accelerate the structure-based drug discovery (SBDD) process. Areas covered : In this review, the authors describe the general principles of X-ray generation and the main properties of XFEL beams, outline details of SFX data collection and processing, and summarize the progress in the development of associated instrumentation for sample delivery and X-ray detection. An overview of the SFX applications to various important drug targets such as membrane proteins is also provided. Expert opinion : While SFX has already made clear advancements toward the understanding of the structure and dynamics of several major drug targets, its robust application in SBDD still needs further developments of new high-throughput techniques for sample production, automation of crystal delivery and data collection, as well as for processing and storage of large amounts of data. The expansion of the available XFEL beamtime is a key to the success of SFX in SBDD.